Pengelolaan Kurikulum Dan Pembelajaran Seni Karawitan Jawa (Studi Situs di SDN Wonosidi II Tulakan Pacitan 2013) - SUWARNO, Suwarno, Prof. Dr. Bambang Sumardjoko, Dr. Samino, M.M (2015)
The objectives of this study are (1) examine about the preparation of Javanese Gamelan Music curriculum; (2) to describe the implementation of Javanese Gamelan Music learning; and (3) examine about the evaluation of Javanese Gamelan Music curriculum at SDN Wonosidi II Tulakan Pacitan. This research is basically a qualitative research with ethnography research design. This study was conducted at SDN Wonosidi II Tulakan Pacitan with the informant consisted of the principal, teacher and students of SDN Wonosidi II Tulakan Pacitan. For data collection method, it used interview, observation and documentation. Data analysis was started from data reduction, data display and drawing conclusion or verification. Data validity used credibility, transferability, confirmability, and dependability. The results of the research show that: (1) preparation of Education Unit Level Curriculum of Javanese Gamelan Music was a collaboration of several parties consisting of the principal, teachers, committee, and stakeholder of SDN Wonosidi II Tulakan Pacitan. The Annual Program created bytecher of local subject Javanese Musical art. The total amount of time allocated was 84 hours of class IV and V, and 86 hours of class VI. Semester Program derived from the anual program. In the syllabus ; Standards of competency, Basic competence , materials, learning activities, indicators, assessment tools, time allocation, and learning resources. Lesson plan drawn up by the teacher includes 9 components and requested approval of the principal. Minimum Kompetenees Creteria estabilished in accordance with the guidelines issued by the National Education Standards . Minimum Kompetenees Creteria score for grade 4 was 65, while grade 5 and 6 was 70. (2) Implementation of Javanese Gamelan Music was started by a greeting from teacher, a motivation and apperception. The instructional methods used included: (a) expository method (explaining), (b) Question and Answer, (c) demonstration, and (d) direct practice. Instructional instrument used was a set of gamelan Slendro and Pelog. (3) Evaluation of Javanese Gamelan Curriculum was ever done at SDN Wonosidi II Tulakan Pacitan. This evaluation aimed at evaluating the extent to which learning programs have been realized. It was done in a micro evaluation. Evaluation model used was the CIPP evaluation model.